Bias Gender dalam Surat Kabar (Analisis Isi Pemberitaan Harian Umum Nasional Waspada Sumatera Utara Edisi 01 Agustus-31 Agustus 2018) - Fitri Rahmadani Angkat (Medan Resource Center, 2021)
This article discusses gender bias in the North Sumatra Waspada National Daily Newspaper, Edition 01 August-31 August 2018. The Waspada General Daily is one of the national newspapers in North Sumatra which still exists and is still active as a news channel. general daily. This newspaper has a vision and mission to deliver true news and does not favor one particular group. This article is a qualitative research with a descriptive approach. The results of the study indicate that the forms of gender bias that are displayed in the news by the General Waspada Daily are stereotypes, subordination, discrimination, and marginalization of women.